Recognition performance and mechanism of the activated carbon based UF resin towards traces of Fe(III) in rare earth solutions. Issue 2 (April 2017) - An, Fu-Qiang; Wu, Rui-Yan; Li, Min; Yuan, Zhi-Guo; Hu, Tuo-Ping; Gao, Jian-Feng
Highlights: A novel activated carbon (ACUF 700) was successfully obtained. The ACUF 700 possesses strong adsorption affinity and excellent recognition selectivity for Fe(III). The adsorption and recognition mechanism of ACUF 700 for Fe(III) is analyzed using XPS method. ACUF 700 could be reused almost without any loss in the adsorption capacity. Abstract: Some trace of non-rare earth impurities has serious damage on the performance of rare earth material. Therefore, efficient removing these impurities from rare earth is very significant. In this paper, a novel activated carbon (ACUF 700) was synthesized by homemade urea formaldehyde resin carbonized at 700 °C. The surface properties, chemical functional groups, element content, surface morphology, and XPS of ACUF 700 were investigated. The adsorption behavior of ACUF 700 towards Fe(III) were investigated by batch and column method. The BET specific surface area of ACUF 700 was 712 cm 3 g −1, and the average pore diameter was 2 nm. The ACUF 700 possesses strong adsorption affinity and excellent recognition selectivity for Fe(III). The adsorption capacity could reach to 13 mg g −1, and relative selectivity coefficients relative to La(III) and Ce(III) was 28.0 and 25.3, respectively. Besides, ACUF 700 could be regenerated easily and reused without losing significantly adsorption capacity.